Recent Development of Ruminant Vaccine Against Viral Diseases - Choudhury, Sk Mohiuddin; Ma, XuSheng; Dang, Wen; Li, YuanYuan; Zheng, HaiXue (Frontiers in Veterinary Science, 2021)
Pathogens of viral origin produce a large variety of infectious diseases in livestock. It is essential to establish the best practices in animal care and an efficient way to stop and prevent infectious diseases that impact animal husbandry. So far, the greatest way to combat the disease is to adopt a vaccine policy. In the fight against infectious diseases, vaccines are very popular. Vaccination's fundamental concept is to utilize particular antigens, either endogenous or exogenous to induce immunity against the antigens or cells. In light of how past emerging and reemerging infectious diseases and pandemics were handled, examining the vaccination methods and technological platforms utilized for the animals may provide some useful insights. New vaccine manufacturing methods have evolved because of developments in technology and medicine and our broad knowledge of immunology, molecular biology, microbiology, and biochemistry, among other basic science disciplines. Genetic engineering, proteomics, and other advanced technologies have aided in implementing novel vaccine theories, resulting in the discovery of new ruminant vaccines and the improvement of existing ones. Subunit vaccines, recombinant vaccines, DNA vaccines, and vectored vaccines are increasingly gaining scientific and public attention as the next generation of vaccines and are being seen as viable replacements to conventional vaccines. Modern ruminant vaccine development methods, among other fundamental science disciplines, have been developed thanks to advances in technology and medicine, as well as our comprehensive knowledge of immunology, molecular biology, microbiology, and biochemistry. The current review looks at the effects and implications of recent ruminant vaccine advances in terms of evolving microbiology, immunology, and molecular biology.